Modeling Water Quality in Dynamic River Systems: Simulating Nutrients and Emerging Contaminants Under Variable Flow Conditions - Wang, Mengyun; Morales-Hernandez, Mario; Brufau, Pilar; Garcia-Navarro, Pilar (Jornada de Jóvenes Investigadores del I3A, 2025)
This study presents a 1D water quality model that integrates hydrodynamics and biochemical processes capable of simulating both conventional indicators and emerging contaminants. The sensitivity analysis highlights the model’s potential in reproducing real water quality dynamics and capturing the behavior of emerging contaminants in dynamic extreme scenarios.